2013
DOI: 10.1016/j.biortech.2013.05.083
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy–split range control system applied to a fermentation process

Abstract: In this study it was proposed the application of a fuzzy-PI controller in tandem with a split range control strategy to regulate the temperature inside a fermentation vat. Simulations were carried out using different configurations of fuzzy controllers and split range combinations for regulatory control. The performance of these control systems were compared using conventional integral of error criteria, the demand of utilities and the control effort. The proposed control system proved able to adequately regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 16 publications
0
10
0
4
Order By: Relevance
“…The temperature control of an alcoholic fermentation process through Takagi-Sugeno modeling is presented in [24]. A fuzzy-split range control system applied to the fermentation process is shown in [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The temperature control of an alcoholic fermentation process through Takagi-Sugeno modeling is presented in [24]. A fuzzy-split range control system applied to the fermentation process is shown in [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The modified Monod equation according to the Michaelis–Menten developed by Aiba [21] gives the cell kinetics of the presented model.μ=μoCsKs+Cse-K1CpThe mathematical models of the fermentation process for the production of alcohol have been developed in the literature and used by various researchers to achieve different control objectives by using different control algorithms. The mathematical models of the bioreactor for the production of ethanol have been developed and implemented for temperature control [[1], [2], [3],[5], [6], [7],20]. Therefore, these mathematical models of the bioreactor are also considered in the present study for temperature control.…”
Section: Modeling Of a Continuous Bioreactormentioning
confidence: 99%
“…A fractional order IMC-PID (FOIMC-PID) and modified fractional order IMC-PID (MFOIMC-PID) were used for temperature control of the bioreactor in the fermentation process and further, a water cycle algorithm was used to optimize the designed controller parameters which lead to WMFOIMC-PID controller [1]. Takagi-Sugeno [5] and fuzzy-PI with split range control [6] were used to control the temperature of the bioreactor of the fermentation process. Pachauri et al [7] suggested two degrees of freedom PID based inferential control for the temperature control of continuous bioreactor in a fermentation process.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, conventional PID controller is not recommended in literature for nonlinear process. Therefore, people are searching some alterative solution in this regard and are inclined towards intelligent techniques such as fuzzy logic control [4,5,6,15]. Therefore, non-linear nature of CSTR requires other methods than conventional control techniques.…”
Section: Introductionmentioning
confidence: 99%